Adenylate kinase 1 overexpression increases locomotor activity in medaka fish. - Michiyo Maruyama; Yuko Furukawa; Masato Kinoshita; Atsushi Mukaiyama; Shuji Akiyama; Takashi Yoshimura (PLoS ONE)
Maintenance of the energy balance is indispensable for cell survival and function. Adenylate kinase (Ak) is a ubiquitous enzyme highly conserved among many organisms. Ak plays an essential role in energy regulation by maintaining adenine nucleotide homeostasis in cells. However, its role at the whole organism level, especially in animal behavior, remains unclear. Here, we established a model using medaka fish (Oryzias latipes) to examine the function of Ak in environmental adaptation. Medaka overexpressing the major Ak isoform Ak1 exhibited increased locomotor activity compared to that of the wild type. Interestingly, this increase was temperature dependent. Our findings suggest that cellular energy balance can modulate locomotor activity.